The effect of addition of methionine and lysine in rations containing fermented palm kernel cake on broiler protein efficiency ratio - M. Alfarizi; Mairizal, Mairizal; Akmal, Akmal (Fakultas Peternakan Universitas Papua, 2025)
This study aims to determine the effect of methionine and lysine supplementation in rations containing fermented palm kernel cake inoculated with Bacillus cereus V9 on the Protein Efficiency Ratio. This study used a completely randomized design (CRD) with five treatments and four replications. The treatments in this study were different levels of methionine and lysine administration in rations containing fermented palm kernel cake. Treatment P0 = is a control ration (RK), namely a ration containing fermented palm kernel cake without the addition of methionine and lysine. P1 = RK + 0.25% lysine and 0.25% Methionine, P2 = RK + 0.5% lysine and 0.25% Methionine, P3 = RK + 0.25% lysine and 0.5% Methionine and P4 = RK + 0.5% lysine and 0.5% Methionine. Observed variables are Feed Consumption, Body Weight Gain, Protein Consumption, and Protein Efficiency Ratio. Data were processed using analysis of variance with Duncan's advanced test. The results of the study showed that the addition of methionine and lysine to rations containing fermented palm kernel meal did not significantly affect (P > 0.05) feed consumption, but significantly affected (P < 0.05) protein consumption, body weight gain, and protein efficiency ratio. The addition of 0.5% methionine and lysine can increase body weight gain, protein intake, and protein efficiency ratio. This study concludes that the addition of 0.5% methionine and 0.5% lysine to rations containing fermented palm kernel meal by Bacillus cereus V9 can increase the protein efficiency ratio.